Analisando a mobilidade de pesquisadores através de registros curriculares na Plataforma Lattes - Chaves, Luiz Carlos Rodrigues (2016)
Scientific research has an important role in the evolution of human knowledge and it has been increasingly encouraged as an object of study. In literature many works are focusing on analysis that exploring and point correlations and motivations of this evolution, but it is known that scientific research has been demonstrated as a very strong link to this development because researchers when used may transfer especially his knowledge to support the problems resolution. In addition, recent work has shown that the mobility of a researcher can ensure positive aspects in productivity, collaboration and internationalization of scientific research. Therefore, in this study it was decided to analyze the patterns of mobility between active or trained researchers in Brazil in teaching and research institutions through the extraction and treatment of locality dependent metrics present in their curriculum vitae records. Because of the scope on the national scene the Lattes Platform was adopted as the primary data source on the researchers mobility history. However mobility analysis was only possible because to extraction methodology and data processing from this work that created the mobility flow of all Lattes doctors using their birth, training and work records in this order to create the metrics and visualizations used in results obtained. With this methodology we could identify the training centers of the most influential human resources for the national scientific community and the network of training institutions and researchers registered activities in the Lattes platform. Even describing how the mobility vary over time. In addition to identifying some interesting patterns of mobility, such as the minimum displacement trend conducted by researchers in various geographical contexts view.